2017
DOI: 10.1016/j.ygyno.2017.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Tissue factor-factor VIIa complex triggers protease activated receptor 2-dependent growth factor release and migration in ovarian cancer

Abstract: Objective Enhanced tissue factor (TF) expression in epithelial ovarian cancer (EOC) is associated with aggressive disease. Our objective was to evaluate the role of the TF-factor VIIa-protease-activated receptor-2 (PAR-2) pathway in human EOC. Methods TCGA RNAseq data from EOC databases were analyzed for PAR expression. Cell and microparticle (MP) associated TF protein expression (Western blot) and MP-associated coagulant activity were determined in human EOC (SKOV-3, OVCAR-3 and CaOV-3) and control cell lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(35 citation statements)
references
References 37 publications
2
32
0
1
Order By: Relevance
“…This may enhance the development of malignant tumors, which suggests that the activation of the coagulation system in certain patients with malignant tumors is closely associated with clinical stage and prognosis ( 13 , 22 ). TFs facilitate the signal transduction of transmembrane proteins in and out of tumor cells and therefore have a greater impact compared with non-transmembrane proteins on the invasion and metastasis of tumor cells ( 23 , 24 ). Previous studies have demonstrated that TF may be activated by forming complexes with coagulation factor VII or VIIa; together with protease activated receptor (PAR)-1 or PAR-2 these complexes may mediate signal transduction within and outside tumor cells ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This may enhance the development of malignant tumors, which suggests that the activation of the coagulation system in certain patients with malignant tumors is closely associated with clinical stage and prognosis ( 13 , 22 ). TFs facilitate the signal transduction of transmembrane proteins in and out of tumor cells and therefore have a greater impact compared with non-transmembrane proteins on the invasion and metastasis of tumor cells ( 23 , 24 ). Previous studies have demonstrated that TF may be activated by forming complexes with coagulation factor VII or VIIa; together with protease activated receptor (PAR)-1 or PAR-2 these complexes may mediate signal transduction within and outside tumor cells ( 23 , 24 ).…”
Section: Discussionmentioning
confidence: 99%
“…TFs facilitate the signal transduction of transmembrane proteins in and out of tumor cells and therefore have a greater impact compared with non-transmembrane proteins on the invasion and metastasis of tumor cells ( 23 , 24 ). Previous studies have demonstrated that TF may be activated by forming complexes with coagulation factor VII or VIIa; together with protease activated receptor (PAR)-1 or PAR-2 these complexes may mediate signal transduction within and outside tumor cells ( 23 , 24 ). Chanakira et al ( 23 ) revealed that the TF/VIIa complex activates PAR-2 to increase the chemotactic migration of epithelial ovarian tumor cells, and in turn promotes disease progression.…”
Section: Discussionmentioning
confidence: 99%
“…They could be helpful molecular tools for teasing out the relative merits of complete versus selective blockade of individual PAR2-linked signaling pathways in cells. In disease settings like cancer, where PAR2 is highly expressed it may be more desirable to inhibit multiple PAR2-dependent signaling associated with metastasis, proliferation, angiogenesis, and other functions promoting tumor development (Dorsam and Gutkind, 2007;Chang et al, 2013;Xie et al, 2015;Chanakira , 2017), whereas in other settings it may be more desirable to dampen some signaling such as that leading to proinflammatory functions while still engaging signaling that leads to beneficial anti-inflammatory actions.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a recent survey of PAR family member expression in human tumor samples of various cancer types from The Cancer Genome Atlas (TCGA) and the Genotype-Tissue Expression projects (GTEx) reveals upregulated PAR-2 in 15 different cancer types compared with normal tissues (16). A global transcriptome array analysis of PAR expression in over 1,000 ovarian cancer and normal tissue samples showed that human epithelial ovarian cancers predominantly overexpress PAR-2, followed closely by PAR-1, with minimal detection of PAR-3 and PAR-4 (32). Consistent with this, increased PAR-2 is associated with poor prognosis and decreased progression-free and overall survival in patients with ovarian, cervical, and hepatocellular carcinoma (30,(33)(34)(35).…”
Section: Par-2 Signaling and Cancermentioning
confidence: 99%